By Eqs. (4-155), (4-157) and (4-170)
Qa[e-1] ~ (sin 4)" (cos ))2J X-(p/2+j)As-- 0, (4-198)
where s = -3 for a t, r and s = -2 for a = .
(ii-2) n q 0
By Eqs. (4-155), (4-157) and (4-171)
Qa [e-] ~ (sin )" p(cos 4)2j X-(p2+j)Rs, (4-199)
where s = -2 for a t, r and s -1 for a = 0, .
Therefore, by analyzing the structure of Qa[-'1] we find that the e-1 terms vanish
in all the cases except when n q = 0. The non-vanishing Ba-terms are derived
only from this case. Then, by 0 < q < 1p + j (p + i), 0 < i < k p and
p < k < 2n together with n = q one can show that
p+i < kandk